Treatment satisfaction and medication adherence among hypertensive patients seeking care in selected hospitals in Ibadan, Nigeria (2018)
Poor adherence to hypertension treatment is a major health-related problem, and a significant risk factor for complications, disability and hypertension associated mortality. There is a paucity of evidence on the impact of treatment satisfaction on medication adherence among hypertensive patients in Nigeria. This study aimed to determine the association between treatment satisfaction and medication adherence among hypertensive patients in Ibadan, Nigeria. A descriptive cross-sectional study was conducted, wherein hypertensive patients were consecutively recruited from 5 hospitals in Ibadan, Nigeria. A pre-tested, interviewer-administered questionnaire was used to collect data. Medication adherence was assessed using the 8-item Morisky Medication Adherence Scale (MMAS-8), and treatment satisfaction using the 9-item Treatment Satisfaction Questionnaire for Medication (TSQM). Descriptive statistics were computed for all variables. Bivariate analysis was carried out using chi-square test, and multivariate analysis using binary logistic regression. Sensitivity analysis was conducted to adjust for unmeasured binary confounders. Statistical significance was set at p < 0.05 for a 2-tailed. A total of 342 respondents with the mean age of 59.6 ± 12.6 years participated in the study. The overall prevalence of medication adherence was 35.1% (MMAS-8 scores = 8). Treatment satisfaction (AOR=2.03, 95% CI: 1.21-3.43) was independently associated with medication adherence. Sensitivity analysis revealed that the observed association between treatment satisfaction and medication adherence was unlikely to be due to unmeasured confounding variables. Medication adherence was low, and treatment satisfaction independently increases medication adherence. Treatment satisfaction strategies should be part of any treatment intervention packages in this population.